(untitled) (Research, Society and Development, 2021)
The present study aimed to identify the relationship between parameters of dietary and erythrocyte selenium and lipid profile markers in women with obesity. This is a case-control study involving 56 women, aged between 20 and 50 years, divided into two groups: case group (obese, n = 22) and control group (eutrophic, n = 34). The concentrations of dietary and erythrocyte selenium and lipid profile (total cholesterol, triacylglycerols, HDL-cholesterol, LDL-cholesterol and VLDL-cholesterol) were evaluated. The project was approved by the Research Ethics Committee of the Federal University of Piauí, under opinion number 2,014,100. The data were analyzed using the statistical program SPSS for Windows 20.0 ®. As for the results, it was observed that the average values of dietary selenium intake were adequate according to the recommendations of the recommended daily intake of 55 µg of selenium (p> 0.05). Obese women had reduced erythrocyte concentrations of selenium when compared to the control group (p <0.05). Regarding the lipid profile, obese women showed high parameters of total cholesterol, triglycerides, LDL-c and VLDL-c and reduced HDL-c values, when compared to the control group (p <0.05). In addition, there was no significant correlation between dietary and erythrocyte selenium and the parameters of the lipid profile between the groups evaluated. In view of the results, the study reveals no correlation between the dietary and erythrocyte selenium marker and the parameters of the lipid profile.